Elucidation of the 'Honeycrisp' pedigree through haplotype analysis with a multi-family integrated SNP linkage map and a large apple (Malus×domestica) pedigree-connected SNP data set. (22nd February 2017) - Howard, Nicholas P; van de Weg, Eric; Bedford, David S; Peace, Cameron P; Vanderzande, Stijn; Clark, Matthew D; Teh, Soon Li; Cai, Lichun; Luby, James J
Abstract: The apple ( Malus×domestica ) cultivar Honeycrisp has become important economically and as a breeding parent. An earlier study with SSR markers indicated the original recorded pedigree of 'Honeycrisp' was incorrect and 'Keepsake' was identified as one putative parent, the other being unknown. The objective of this study was to verify 'Keepsake' as a parent and identify and genetically describe the unknown parent and its grandparents. A multi-family based dense and high-quality integrated SNP map was created using the apple 8 K Illumina Infinium SNP array. This map was used alongside a large pedigree-connected data set from the RosBREED project to build extended SNP haplotypes and to identify pedigree relationships. 'Keepsake' was verified as one parent of 'Honeycrisp' and 'Duchess of Oldenburg' and 'Golden Delicious' were identified as grandparents through the unknown parent. Following this finding, siblings of 'Honeycrisp' were identified using the SNP data. Breeding records from several of these siblings suggested that the previously unreported parent is a University of Minnesota selection, MN1627. This selection is no longer available, but now is genetically described through imputed SNP haplotypes. We also present the mosaic grandparental composition of 'Honeycrisp' for each of its 17 chromosome pairs. This new pedigree and genetic information will be useful in future pedigree-based genetic studies to connect 'Honeycrisp' with other cultivars used widely in apple breeding programs. The created SNP linkage map will benefit future research using the data from the Illumina apple 8 and 20 K and Affymetrix 480 K SNP arrays. Abstract : Apples: 'Honeycrisp' pedigree revealed by DNA analysis A genetic analysis has revealed the true pedigree of the popular 'Honeycrisp' variety of apple. James Luby from the University of Minnesota, USA, and colleagues wanted to determine the correct parentage of 'Honeycrisp'. They created a genetic map based on 8, 000 single DNA letters, and found that the originally recorded parentage, a cross between 'Honeygold' and 'Macoun', was wrong. They confirmed that one parent was 'Keepsake'. The other parent seemed to be a cross between 'Duchess of Oldenburg' and 'Golden Delicious' from an unknown source. Using the genetic data, they identified related varieties of 'Honeycrisp'. Breeding records from several of these close relatives pointed to the enigmatic parent: MN1627, a variety from the University of Minnesota now thought to be extinct. The new pedigree and genetic information for 'Honeycrisp' apples should help in future breeding programs.